2014
DOI: 10.1128/jvi.03431-13
|View full text |Cite
|
Sign up to set email alerts
|

Relative Roles of GM1 Ganglioside, N -Acylneuraminic Acids, and α2β1 Integrin in Mediating Rotavirus Infection

Abstract: N-acetyl-and N-glycolylneuraminic acids (Sia) and ␣2␤1 integrin are frequently used by rotaviruses as cellular receptors through recognition by virion spike protein VP4. The VP4 subunit VP8*, derived from Wa rotavirus, binds the internal N-acetylneuraminic acid on ganglioside GM1. Wa infection is increased by enhanced internal Sia access following terminal Sia removal from main glycan chains with sialidase. The GM1 ligand cholera toxin B (CTB) reduces Wa infectivity. Here, we found sialidase treatment increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 80 publications
0
37
0
1
Order By: Relevance
“…To validate protein activity, an equimolar concentration of GM1a glycan, a confirmed receptor for the DS-1-like P [4] rotavirus strain RV-5 and for RV-3 (ref. 22) was added to the A-tri complex of VP8* protein from DS-1 or RV-3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To validate protein activity, an equimolar concentration of GM1a glycan, a confirmed receptor for the DS-1-like P [4] rotavirus strain RV-5 and for RV-3 (ref. 22) was added to the A-tri complex of VP8* protein from DS-1 or RV-3.…”
Section: Resultsmentioning
confidence: 99%
“…Binding by GST-VP8* from HAL1166, K8 and Wa rotaviruses to MA104 cells was assayed in the same experiment at 4°C as previously described 22 . The optimal (saturating) concentration of each GST-VP8* was initially determined from its dose-dependent cell-binding curve.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent observations show that not all rotaviruses require a sialic acid determinant for binding (49,74,93). Based on the studies reported here, it is important that the so-called neuraminidase-insensitive or sialic-acid-independent rotaviruses be analyzed for their glycan binding specificities on similar shotgun glycan microarrays comprising milk glycans or glycans released from cells or tissues susceptible to rotavirus infection.…”
Section: Specific Lectins and Antibodies Identify Determinants Of Thementioning
confidence: 99%